2021
DOI: 10.3389/fendo.2021.700884
|View full text |Cite
|
Sign up to set email alerts
|

Motilin Comparative Study: Structure, Distribution, Receptors, and Gastrointestinal Motility

Abstract: Motilin, produced in endocrine cells in the mucosa of the upper intestine, is an important regulator of gastrointestinal (GI) motility and mediates the phase III of interdigestive migrating motor complex (MMC) in the stomach of humans, dogs and house musk shrews through the specific motilin receptor (MLN-R). Motilin-induced MMC contributes to the maintenance of normal GI functions and transmits a hunger signal from the stomach to the brain. Motilin has been identified in various mammals, but the physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 221 publications
(527 reference statements)
1
22
2
1
Order By: Relevance
“…Motilin is found within the mammalian kingdom, with orthologues identified in birds, reptiles, amphibians, and fishes; the receptor for motilin, a seven‐transmembrane (TM), G‐protein‐coupled structure (first identified in human 10 ), has a matching presence. 11 , 12 , 13 However, examinations of genomic databases, including those assembled by Ensembl, found that among the mammals, the genes in rodents (mouse, rat, kangaroo rat, guinea pig, squirrel, a strain of pika) for the motilin receptor and often for motilin itself, have become pseudogenes (e.g., 80%–90% identity to the human motilin receptor, but with an in‐frame stop‐codon). This indicates that in rodents the functions of motilin have been lost 11 , 12 , 14 , 15 For the mouse and rat, this is thought to have occurred via mutations in the genes encoding the motilin receptor and motilin, and not by a disruptive chromosomal rearrangement that potentially could have removed both genes.…”
Section: Loss Of a Functional Motilin System Among Rodentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Motilin is found within the mammalian kingdom, with orthologues identified in birds, reptiles, amphibians, and fishes; the receptor for motilin, a seven‐transmembrane (TM), G‐protein‐coupled structure (first identified in human 10 ), has a matching presence. 11 , 12 , 13 However, examinations of genomic databases, including those assembled by Ensembl, found that among the mammals, the genes in rodents (mouse, rat, kangaroo rat, guinea pig, squirrel, a strain of pika) for the motilin receptor and often for motilin itself, have become pseudogenes (e.g., 80%–90% identity to the human motilin receptor, but with an in‐frame stop‐codon). This indicates that in rodents the functions of motilin have been lost 11 , 12 , 14 , 15 For the mouse and rat, this is thought to have occurred via mutations in the genes encoding the motilin receptor and motilin, and not by a disruptive chromosomal rearrangement that potentially could have removed both genes.…”
Section: Loss Of a Functional Motilin System Among Rodentsmentioning
confidence: 99%
“… Is the variation in response to motilin characteristic for functions that are undergoing gene pseudonymization? In different species of rodent, He et al 11 , 18 described the complete loss of functional genes for motilin and its receptor, but in others, a functional motilin gene remained whilst the receptor was non‐functional (the opposite may be true in certain amphibians 13 ). This variation was argued to have been brought about by early pseudonymization of the motilin receptor followed by progressive pseudonymization of the motilin gene during the evolution of the Rodentia order.…”
Section: Conclusion and Questionsmentioning
confidence: 99%
See 3 more Smart Citations